2007
DOI: 10.1128/aem.00156-07
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Activity and Spatial Organization of Anaerobic Ammonium-Oxidizing (Anammox) Bacteria in Biofilms

Abstract: We investigated autotrophic anaerobic ammonium-oxidizing (anammox) biofilms for their spatial organization, community composition, and in situ activities by using molecular biological techniques combined with microelectrodes. Results of phylogenetic analysis and fluorescence in situ hybridization (FISH) revealed that "Brocadia"-like anammox bacteria that hybridized with the Amx820 probe dominated, with 60 to 92% of total bacteria in the upper part (<1,000 m) of the biofilm, where high anammox activity was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(63 citation statements)
references
References 49 publications
4
59
0
Order By: Relevance
“…Anammoxoglobus," and "Ca. Kuenenia" lineages are usually associated with wastewater processing systems, freshwater, or diverse terrestrial environments (27,(31)(32)(33)77). It is possible that some anammox bacteria are more resistant to stressful and adverse environmental changes than others (5), which may explain that anammox bacteria belonging to predominantly nonmarine cohorts can survive in marine environments at low numbers without detectable anammox activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Anammoxoglobus," and "Ca. Kuenenia" lineages are usually associated with wastewater processing systems, freshwater, or diverse terrestrial environments (27,(31)(32)(33)77). It is possible that some anammox bacteria are more resistant to stressful and adverse environmental changes than others (5), which may explain that anammox bacteria belonging to predominantly nonmarine cohorts can survive in marine environments at low numbers without detectable anammox activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Originally considered to be inhibited by organic matter, some anammox species are less inhibited by carbon [46] and some of the most recently discovered species flourish when organic matter is present. Kindaichi [47] postulated that anammox was inhibited by COD; but probably a result of species, pH, temperature, type of carbon, and C:N ratio. Molinuevo's work [48] appeared to indicate that organic matter at high COD concentrations (100 to 250 mg COD/L) negatively affected the anammox process and facilitated heterotrophic denitrification, but at COD concentrations < 100 mg/L, anammox bacteria successfully converted ammonium to nitrogen gas suggesting that anammox removal of nitrogen of already treated wastewater having low COD is quite possible.…”
Section: Wastewater Treatment Systems Using Anammoxmentioning
confidence: 99%
“…Furthermore, the cultures showed a low population density (67-90% of total bacteria) and/or low conversion rates (0.07-0.35 g L −1 day −1 ) after long periods of enrichment. We previously reported that anammox bacteria derived from wastewater were successfully enriched using up-flow fixed-bed column reactors, and that the anammox reaction was observed within 2-3 months after the reactor start-up (14,33). These studies were conducted based on strategies specific for the selected inoculum and a short hydraulic retention time (HRT).…”
mentioning
confidence: 99%